Aplikasi Jenis Dan Dosis Pupuk Organik Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Putih (Brassica pekinensia L) - I Made Yudi Martadinata; I Gusti Bagus Udayana; Made Sri Yuliartini (GEMA AGRO, 2021)
The purpose of this study is determine the application of the type and dosage of organic fertilizers on the growth and yield of chicory plant (Brassica pekinensia L). The hypothesis that proposed in this study is that with the chicken manure at a dose of 10 tonnes / ha can provide growth and higher crop yield of chicory plants. The research design that used in this study is the randomized block design (nested RAK), where the nested dose was added to each type of fertilizer and one control was added. The type of fertilizer are cow manure (Ps), chicken manure (Pa), and goat manure (Pk), and the doses used are D1 (5 tons / ha), D2 (10 tons / ha), and D3 (15 tons / ha). The experiment in the field which was carried out from February 2020 to April 2020 in the moor, in Pemuteran Backwoods, Pempatan village Rendang District, Karangasem Regency with an altitude of around 650 m above sea level. The higher fresh weight of crop was founding from chicken manure, that is 445.22 gram, which not different significantly from cow manure that is 439.63 gram and goat manure that is 433.74 gram. Cow manure, chicken manure and goat manure at a dose of 15 tones per hectare gave high fresh crop weight, namely 483.43 gram, 467.50 gram and 488.15 gram which were not different significantly compared to other treatment and control.